MULTICRITERION PROBLEM OF OPERATIVE EDITING OF SCHEDULES - YAKHNO, VOLODYMYR; DEMKIVSKA, TETIANA; ASTISTOVA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This paper presents a technology that allows for quick editing of the calendar plan for the execution of independent tasks (works) by different independent performers. A formal model and algorithm for studying the task of editing the calendar plan for the execution of independent tasks by different independent performers (participants in the works) are considered. Performers have their own ideas about the quality of the schedule but use common resources. A partial case of the task is the schedule of classes in a higher educational institution. An algorithm is proposed that allows for improving or quick editing of the calendar plan so that all changes satisfy the requirements of all participants in the process. The task is typical and can be applied in many cases of operational dispatch planning.The development of calendar plans for the execution of independent tasks by different independent performers should be implemented in two stages. The first stage is the formation of the initial plan, the second is editing in accordance with the wishes of individual performers. At the second stage, algorithms are needed that allow for the transformation of the known schedule in accordance with the informal wishes of the participants in the process. One of the processes that illustrates such a two-stage planning technology is the class schedule in a higher educational institution.To implement the task, an analysis of the problems that arise during the preparation of schedules was conducted, formal models were formulated for a wide range of problems that arise, and an algorithm for improving the calendar plan for the performance of independent tasks (works) by various independent performers (participants in the works) was proposed.
Keywords: models of operational planning tasks; scheduling theory; class schedule